Injury rates in Major League Baseball during the 2020 COVID-19 season - Platt, B. N.; Uhl, T. L.; Sciascia, A. D.; Zacharias, A. J.; Lemaster, N. G.; Stone, A. V. (Orthopaedic Journal of Sports Medicine, 2021)
Background: The 2020 Major League Baseball (MLB) season was drastically altered because of the COVID-19 pandemic. The changes included an extended layoff between March and July as well as a shortened preseason. Purpose/Hypothesis: To determine the incidence and epidemiology of MLB injuries in the abbreviated 2020 season compared with prior seasons. We hypothesized that there was an increase in the overall injury rate in the 2020 season compared with the 2018-2019 seasons and that it equally affected all body regions. Study Design: Descriptive epidemiology study. Methods: The MLB transactions database was queried to find players who had been placed on the injury list between 2018 and 2020. Injuries were categorized into upper extremity, lower extremity, spine/core, and other injuries. Incidence per 1000 athlete-exposures was calculated for the prior 2 seasons (2018-2019) and for the 2020 season separately. Incidence for each category was also calculated separately for pitchers and fielders. Incidence rate ratios (IRRs) and confidence intervals were used to compare injury rates in 2018-2019 versus 2020. The z test for proportions was used to determine significant differences between injury incidences. Results: In 2020, the overall incidence rate per 1000 athlete-exposures was almost twice the rate compared with the 2 seasons before COVID-19 (8.66 vs 5.13; IRR, 1.69 [95% CI, 1.53-1.87]; P < .001). Injury incidence increased similarly in 2020 for both pitchers (IRR, 1.68 [95% CI, 1.47-1.91]; P < .001) and fielders (IRR, 1.68 [95% CI, 1.45-1.96]; P < .001). Increases in injury incidence were seen in the upper extremity, spine/core, and other injury categories; however, the incidence of the lower extremity did not change significantly. Conclusion: There was a significant increase in injury incidence for both pitchers and fielders in 2020. Injury rates increased in anatomic zones of the upper extremity and spine/core but were not significantly changed in the lower extremity. The overall increase in injury rate suggests that irregular or insufficient sport-specific preparation prior to the start of the season placed athletes at a greater risk of injury when play resumed.